The Relationship Between Simple Isometric Mid-Thigh Pull and Jumping Abilities: A Case Series Study - Junpei Shiba; Hana Yamase; Shota Enoki (International Universities Strength and Conditioning Association, 2023)
Isometric mid-thigh pull (IMTP) is used to measure and monitor the peak force and the rate of force development. However, current IMTP implementation is costly and time-consuming. Thus, a quick, lowcost, and easy method is needed to monitor muscle strength. This case series study aimed to examine the relationship between IMTP assessed using a back strength dynamometer and jumping abilities and determine whether relative strength (N/body weight [BW]) can indicate jumping abilities. Eleven female collegiate basketball players in division III female Tokai Student Basketball League participated in this study. A back strength dynamometer was used to measure IMTP. The starting posture was a 145  relative angle at the knee and hip joints with the chain extended. Jumping measurements were performed for squat jump (SJ), countermovement jump (CMJ), and rebound jump (RJ) using a jump mat.   Additionally, the highest rebound jump index (RJI), jump height, and ground contact time for the highest RJI were used in the statistical analysis. Participants were divided into high (HG) and low (LG) groups based on the median value of relative strength. Cohen's d as an effect size (ES) with a 95% confidence interval was used to compare the jumping abilities between the groups. The relationship between relative strength and jumping abilities was determined using Pearson's correlation coefficient. The HG showed significantly moderate ES for SJ height (d=1.19), CMJ height (d=1.08), RJ height (d=1.19), and ground contact time (d=0.83) and significantly larger ES for RJI (d=1.36) relative to those of the LG. In addition, no significant correlations were observed between relative strength and any of the jump measures. However, relative strength exhibited a moderate correlation coefficient for the correlation between RJI and ground contact time. Therefore, IMTP assessed using a back strength dynamometer can be used to monitor muscle variables related to jumping abilities at a lower cost and training time than those of conventional methods.